The circles of life (6) Get on your cycle - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The circles of life (6) Get on your cycleDo not move. If you must move, do so with caution. If we look for one word around which agriculture and rural development in ACP countries could revolve in the first decades of the new millennium, it could be...